Fluid mechanics - Munson, Bruce R.; Okiishi, Theodore H.; Huebsch, Wade W.; Rothmayer, Alric P. (Wiley Pte. Ltd., 2013)
Fundamentals of Fluid Mechanics offers comprehensive topical coverage, with varied examples and problems, application of visual component of fluid mechanics, and strong focus on effective learning. The text enables the gradual development of confidence in problem solving